MIGRATING THROUGH HYBRID SPACE: NEW EVIDENCE OF CONCEPTUAL UPDATES - de Souza e Silva, Adriana; Avila, Ana; Campbell, Scott W. (AoIR Selected Papers of Internet Research, 2026)
This submission reports on new research that leverages the updated model of Hybrid Space by recognizing the power dynamics – particularly unevenness in access, agency, and awareness – present in the way people experience (and produce) Hybrid Spaces. We demonstrate the unevenness of Hybrid Space by presenting findings from new research investigating the role of mobile media in the migration journey from Central and South America to the U.S. Southern border. Using on-site fieldwork and interviews, this research draws from Hybrid Space to examine how connectivity, mobilities, and sociability shape how people experience migration. The case of migration provides unique opportunities to leverage the conceptual extensions of Hybrid Space, while shifting its lens beyond the traditional focus on cities and urban settings. The precarious conditions of the migration journey offer traction for examining how power dynamics unfold through access, agency, and awareness. We take up these power dimensions of Hybrid Space to structure a discussion of findings from the migration study to illustrate conceptual updates.